P01.040 Identification of a predictive biomarker of response to regorafenib in relapsed glioblastoma patients <REGOMA trial>. (19th September 2018) - Lombardi, G; Indraccolo, S; de Salvo, G; Verza, M; Magni, G; Eoli, M; Rudà, R; Franceschi, E; Faedi, M; Lolli, I; Rizzato, S; Caccese, M; et al.
Abstract: Background: There is currently no predictive biomarker for anti-angiogenic drugs which could be used for patient selection purposes. Pre-clinical studies show that anti-angiogenic therapy exacerbates tumor hypoxia and activatesliver kinase B1 (LKB1)/AMP kinase (AMPK), a pathway involved in the regulation of tumor metabolism. Inspired by these findings, we investigated whether certain angiogenesis- and metabolism-related in situ biomarkers could predict response to regorafenib in the context of the phase 2 randomized REGOMA trial. Material and Methods: Immunohistochemistry was used to investigate expression in tumor sections of vascular endothelial growth factor receptor 2 (VEGFR2), platelet-derived growth factor β (PDGFRβ), fibroblast growth factor receptor (FGFR), the angiopoietin receptor (Tie2), monocarboxylate transporter 1 and 4 (MCT1, MCT4), phosphorylated AMPK (pAMPK) and phosphorylated acetyl-CoA carboxylase(pACC), which is a canonical target of AMPK activity.Positivity for the markers was independently assessed by two analists blinded to clinical data and results of the REGOMA trial. The status of each biomarker was associated with clinical endpoints, including overall survival (OS) and progression free survival (PFS) in patients (PTS) with relapsed GBM treated either with regorafenib or lomustine. Radiological assessment was performed by RANO criteria. Results: Between November 2015 and February 2017, 119 PTS were enrolled ﴾n=59 REG; n=60 LOM﴿ and stratified for surgery at recurrence; baseline characteristics were balanced. Biomarker analysis was performed in 85 PTS (71%), including 43 PTS of the REG arm and 42 PTS of the LOM arm. Among all markers analyzed, only pACC showed predictive value. In fact, median OS was 8.0 months (m) (95% CI 5.6-) for REG and 5.3m (95% CI 4.2–6.6) for LOM for pACC positive patients. HR 0.44 (95% CI 0.22–0.87), log rank p-value = 0.012; Test for interaction = 0.0419. Conclusion: In this randomized, controlled study we report for the first time a predictive impact of pACC expression in patients with relapsed GBM treated with regorafenib. These results suggest that integrity of the AMPK pathway is associated with clinical benefit from treatment with regorafenib.